Job Satisfaction as A Mediating Factor Between Competence, Training, and Turnover Intention Employee - Nila Fatihatur Rohmah; Hesty Prima Rini (SAFE-Network, 2026)
The high desire of employees to change jobs is a serious challenge for companies because it can disrupt operational smoothness and reduce productivity. The purpose of this research is to evaluate how skills and training affect employee turnover, using job satisfaction as an intermediary factor among full-time staff in the CLC operational division. A quantitative approach was applied by distributing Likert-scale questionnaires, using a technical census to all permanent employees of the operational division as respondents. The gathered information was analyzed utilizing a Structural Equation Modeling (SEM) method that focuses on Partial Least Squares (PLS), facilitated by the SmartPLS application. Employee desire to leave the company is often reduce by enhancing competence and offering effective training, according to findings. It has also been demonstrated that job satisfaction is crucial in bridging the gap between training and skill and a high turnover rate. This emphasizes the importance of placing employees according to competence and developing more systematic training programs to increase job satisfaction and reduce turnover rates. Therefore, CLC is recommend to incorporate continuous competence development and training as part of a long-term strategy for employee retention.